On Item Count Technique in Survey Sampling - Hussain, Zawar; Shabbir, Javid (Journal of Informatics and Mathematical Sciences, 2010)
In this paper, an improved Item Count Technique (ICT) has been proposed. The major advantage of this technique is that it does not require two subsamples (as is the case in usual ICT) and there is no need of finding optimum subsample sizes. The proposed ICT has been observed performing well, as compared to the usual ICT, in terms of relative efficiency. The novel method of Randomized Response (RR) technique proposed by Warner (1965) has also been compared with the proposed ICT and it is found that the proposed technique uniformly performs better when the number of innocuous items is greater than 3.